S=t1/(1-r)
r must be 3/8 because 3/8 is multiplied by t each time
S=(3/2)/(1-(3/8))
S=2.4
I hope that this helps.
2007-01-08 14:56:06
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
The equation for the sum of a geometric series is a/(1 - r), where
a: the first term of the series...and
r: the ratio (number) that the term is multiplied by to obtain the next term.
In this case, a = 3/2, and r = 3/8.
The sum is then...
(3/2)/(1 - 3/8)
= (3/2) / (5/8)
= (3/2) * (8/5)
= 24/10
= 12/5
= 2.40, so C
2007-01-08 14:58:49
·
answer #2
·
answered by purpicita_LM_es_fg_MDK 2
·
0⤊
0⤋
For an infinite geometric series, the formula is
S = a1/(1 - r)
Where a1 = the first term
r = the ratio.
In this case, r = 3/8 and a1 = 3/2. Therefore
S = (3/2) / (1 - 3/8)
S = (3/2) / (5/8) = (3/2) * (8/5) = 12/5.
Convert 12/5 to decimal, and you get 24/10, or 2.4.
2007-01-08 14:58:09
·
answer #3
·
answered by Puggy 7
·
0⤊
0⤋
Sum =a/(1-r), where r is the common multiplier and a is the first term in the series.
The common multiplier in this case is r = 3/8 and a = 3/2.
So go get the sum.
2007-01-08 14:56:25
·
answer #4
·
answered by ironduke8159 7
·
0⤊
0⤋
OK here's the equation for the infinite geometric series when the absolute value of R, | R | , < 1 :
S = a1 (A sub 1) / 1 - R
Good luck
2007-01-08 14:55:51
·
answer #5
·
answered by nivi12300 2
·
0⤊
0⤋
S= a / (1-r)
a is the first term and r is the rate at which it increases so for this a would be 3/2 r would be .375
you plug those in the formula and you get 2.4 which is c
2007-01-08 15:01:49
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋